Challenges and obstacles of small and medium enterprises under a creative economy: The case of Thailand - Priya Pholphirul (2018)
Most Small and Medium Enterprises (SMEs) have acquired the status of being either creators or outsourcers, the latter referring to SMEs that are part of the production chain of large companies. Different roles in the production value chain lead to business strategies that vary for each type of creative industry. Those SMEs face many obstacles and challenges such as an inability to meet the needs of the consumer, reliance on large companies for the distribution or delivery of their products to the market (the humdrum factor); problems adapting existing products to suit the needs of some markets; overlooking the importance of Intellectual Property (IP) registration for creative products and not being able to obtain adequate sources of funding especially for those that do not have the necessary collateral. Therefore, the following strategies have been proposed in order to develop SMEs into becoming creative enterprises, namely; modifying the organizational structure; creating a business network; creating unique business strategies; focusing on public relations; market development by utilizing electronic commerce and by creating strong commitment within the organization. Business strategies that suit a creative economy are different for each type of organization; different for each organizations role in the production chain and as mentioned before, different for each type of creative industry. The challenge for an entrepreneur is to develop the organization towards becoming a creative enterprise that has been able to find a structure that is a perfect fit. © Medwell Journals, 2012.